Entrer en collection. Pour une ethnographie des gestes et des techniques de collecte - Julien Bondaz (Les Cahiers de l'École du Louvre)
While the activity of collecting refers to the transformation of artefacts or products of nature into objects of collection, it is necessary to examine the diversity of the gestures and techniques that enable such an operation to be carried out. On the basis of the examples concerning collecting in Africa, it is possible to outline the various issues relating to the entrance into a collection of objects, particularly of their promotion to the status of ethnographical specimen or work of art. It would be advisable to establish an ethnography of the practices of collecting and to show that, far from being univocal, it – from its methods to its encounter with the paradigm of the hunt or market logic – demonstrates a complexity and a heterogeneity that should be examined.